Analisis Biaya Produksi Guna Menentukan Harga Jual : Studi Kasus: Tambak Udang Venambak - Rahmad Efendy; Arman Syukur Zai; Anggi Dian Syafitri; Roma Pasaribu; Nurhasanah Sihotang (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to analyze in depth the structure of production cost components and determine a reasonable and competitive selling price for shrimp farming in the Venambak Shrimp Farm. The background of this study is the need to determine the cost efficiency and profit potential of shrimp farming activities, so that business actors can make the right decisions and be oriented towards sustainability. The study uses a quantitative descriptive approach with the full costing method to calculate the total production costs, and the cost plus pricing method to determine the selling price. The data used consists of primary data, such as details of operational expenses during one cultivation cycle (six months), as well as secondary data obtained from internal company reports and records. The results of the analysis show that the total production costs incurred in one shrimp cultivation cycle reached Rp16,085,208,000, with a total harvest of 1,000,000 kg. Based on these figures, the cost of goods manufactured (COGS) was obtained at Rp16,085 per kg. In determining the selling price, the company used the cost plus pricing method and set the selling price at Rp80,000 per kg. Thus, the profit margin obtained by the company reached Rp63,915 per kg. Gross profit generated during one cultivation cycle reached Rp63,915,000,000. If cultivation were conducted in two cycles per year, the annual gross profit could potentially increase to Rp127,830,000,000. These findings indicate that with efficient cost management and the right pricing strategy, shrimp farming has significant profit potential. Therefore, intensive and sustainable shrimp farming development at the Venambak Shrimp Farm is highly feasible to improve the competitiveness and welfare of fisheries business actors.